2018
DOI: 10.18267/j.aop.599
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Microfinance on Entrepreneurship in Kyrgyzstan

Abstract: The concept of microfinance has developed rapidly since its inception in 1976. Despite its development, the impact it has on entrepreneurship is a subject of debate. Scholarly articles have recently emerged outlining that successful entrepreneurship depends on individual and household characteristics, and on the status of the microfinance loan received. This paper investigates the impact of microfinance on entrepreneurship in Kyrgyzstan using the nationally representative household survey data for 2013. Due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Spinelli & Adam (2012) observed that most of the big businesses available are assumed to have been started as a small business. Microfinance is widely recognized as a crucial tool for poverty alleviation and socio-economic well-being (Sultakeev, Karymshakov, & Sulaimanova, 2105). SMEs play a significant role in stabilizing and in the development of emerging economies.…”
Section: Introductionmentioning
confidence: 99%
“…Spinelli & Adam (2012) observed that most of the big businesses available are assumed to have been started as a small business. Microfinance is widely recognized as a crucial tool for poverty alleviation and socio-economic well-being (Sultakeev, Karymshakov, & Sulaimanova, 2105). SMEs play a significant role in stabilizing and in the development of emerging economies.…”
Section: Introductionmentioning
confidence: 99%
“…It is known for providing credit to all people. According to Sultakeev et al (2018), most successful small-to medium-sized entrepreneurs depend on the loans that they are being granted by MFIs.…”
Section: Literature Review the Concept Of Microfinancementioning
confidence: 99%
“…The research suggests that regulations by micro finance banks to fund young entrepreneurs need to be flexible to fit all the business owners only when banks values and offer technical assistant to the entrepreneurs will be contributing to the entrepreneurs to make sure success in the young entrepreneurs. Sultakeev, Karymshakov and Sulaimanova (2018) performed a study to evaluate the impact of microfinance on entrepreneurial success of China young entrepreneurs. Embracing explanatory study design with a sample which makes up 461 proprietors of SMEs in Shanghai Region data gathering was through questionnaire administering that utilized Likert scale-type questions.…”
Section: Stratford Peer Reviewed Journals and Book Publishing Journal...mentioning
confidence: 99%